Evaluation of dynamics, demography and estimation of free-roaming dog population in Herat City, Afghanistan - Nasiry, Zabihullah; Mazlan, Mazlina; Noordin, Mustapha M.; Mohd Lila, Mohd Azmi (Multidisciplinary Digital Publishing Institute, 2023)
FRDs pose a serious challenge in countries where dog-bite-related rabies is endemic. Understanding the size and core demographic characteristics of FRD populations is essential for the planning and implementation of effective dog-population and canine-rabies-control programmes. The photographic sight–resight method was used to estimate the FRD population and evaluate its demographic characteristics in Herat city. A total of 928 free-roaming dogs (FRD) were identified through 3172 sightings, and the total free-roaming population was estimated to amount to 1821 (95% CI: 1565–2077), which led to the estimation of 10 dogs/km2 and the human-to-FRD ratio of 315:1. The male-to-female ratio was 2.85:1. The majority of them were healthy, with an ideal body score. Although the FRD density is considered low, it is still a concern and significant, since the majority of the people are unaware of the importance of canine populations in the transmission of zoonotic diseases such as rabies, and there were no specific measures for managing and controlling FRD populations. The information gained can be useful in animal health planning to design effective dog-population-control programmes, and for the planning of national rabies-prevention programmes.